2014
DOI: 10.1111/anae.12756
|View full text |Cite
|
Sign up to set email alerts
|

Psychological outcomes in critically ill patients receiving renal replacement therapy: a matched‐pairs analysis

Abstract: SummaryWe conducted a single-centre observational study over five years to assess the impact of renal replacement therapy on the psychological health of survivors of critical illness. We hypothesised that the added burden of renal replacement would increase the prevalence and severity of anxiety, depression and stress reactions in these patients, compared with matched pairs (matched for age, sex and APACHE II score) who did not receive renal replacement. Participants completed postal questionnaires. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The severity of illness and the duration of the illness may be more important predictors of emotional health deficits than the development AKI [21]. A previous study revealed that patients surviving ICU that required acute RRT also did not have differences in emotional health when compared to matched survivors not requiring RRT [20]. Thus, emotional and cognitive health outcomes may not be different simply due to the traumatic experience of critical illness for all ICU survivors independent of the occurrence of AKI and/or need of RRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of illness and the duration of the illness may be more important predictors of emotional health deficits than the development AKI [21]. A previous study revealed that patients surviving ICU that required acute RRT also did not have differences in emotional health when compared to matched survivors not requiring RRT [20]. Thus, emotional and cognitive health outcomes may not be different simply due to the traumatic experience of critical illness for all ICU survivors independent of the occurrence of AKI and/or need of RRT.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors of critical illness who suffer physical, cognitive or emotional impairments have difficulties with activities of daily living [12], reduced likelihood of returning to work [13] and driving [14], and overall worse healthrelated quality of life scores (HRQOL) [15]. The receipt of renal replacement therapy (RRT) has been recognized as a potential risk factor for developing physical impairments [16][17][18], and emotional health symptoms [19,20] in ICU survivors. However, incident AKI has not been comprehensively studied as a risk factor for worse patient-centered outcomes, particularly in survivors of critical illness.…”
Section: Introductionmentioning
confidence: 99%